The Influence of the Discovery Learning Approach with Quizizz Paper Mode Media on Improving Mathematics Scores - Rustanti, Dwi; Huda, Nuril (PT. Anagata Sembagi Education, 2025)
This study aims to determine the effect of the discovery learning model with the help of quizizz paper mode media on increasing the average mathematics scores of grade 3 students of Segorotambak State Elementary School, Sedati District, Sidoarjo as an experimental group. The background of this study is the large number of students who have mathematics scores below the KKM (Minimum Completion Criteria). In this study, there are 2 population groups, namely Segorotambak State Elementary School as an experimental group using the discovery learning model with the help of quizizz paper mode and Pepe State Elementary School as a control group. This study uses a quantitative experimental research type with a pre-Experimental Design One-Group (Pretest-Posttest Design) research design. The population used was grade 3 of Pepe State Elementary School totaling 28 students and Segorotambak State Elementary School totaling 17 students. Data collection techniques in the form of giving an initial test (pre-test) before being given treatment and a final test (post-test). The data analysis technique used in this study was the results obtained from the pre-test and post-test scores of students using Shapiro Wilk. The results of this study showed a significant increase in the average value from 49.41, after using the Discovery Learning approach with the help of quizizz paper mode media to 70.58 or an increase of 21.17 so that research with the discovery learning approach through quizizz paper mode media at Segorotambak State Elementary School has been proven to be able to improve the mathematics scores of students in the experimental group.